V-ATPase regulates communication between microvascular endothelial cells and metastatic cells - Sennoune, S. R.; Arutunyan, A.; Del rosario, C.; Castro-marin, R.; Hussain, F.; Martinez-zaguilan, R. (Cellular and Molecular Biology, 2014)
To metastasize distant organs, tumor cells and endothelial cells lining the blood vessels must crosstalk. The nature of this communication that allows metastatic cells to intravasate and travel through the circulation and to extravasate to colonize different organs is poorly understood. In this study, we evaluated one of the first steps in this process - the proximity and physical interaction of endothelial and metastatic cells. To do this, we developed a cell separator chamber that allows endothelial and metastatic cells to grow side by side. We have shown in our previous studies that V-ATPases at the cell surface (pmV-ATPase) are involved in angiogenesis and metastasis. Therefore, we hypothesized that the physical proximity/interaction between endothelial and metastatic cells expressing pmV-ATPase will increase its activity in both cell types, and such activity in turn will increase pmV-ATPase expression on the membranes of both cell types. To determine pmV-ATPase activity we measured the proton fluxes (JH+) across the cell membrane. Our data indicated that interaction between endothelial and metastatic cells elicited a significant increase of JH+ via pmV-ATPase in both cell types. Bafilomycin, a V-ATPase inhibitor, significantly decrease JH+. In contrast, JH+ of the non-metastatic cells were not affected by the endothelial cells and vice-versa. Altogether, our data reveal that one of the early consequences of endothelial and metastatic cell interaction is an increase in pmV-ATPase that helps to acidify the extracellular medium and favors protease activity. These data emphasize the significance of the acidic tumor microenvironment enhancing a metastatic and invasive phenotype.